G95(P) Druggle: a prescribing safety quality improvement project. (25th October 2020) - Clubb, R; Mehta, N; Kalaivanan, P
Abstract : Aim: Prescription errors are common on paediatric wards and have the potential to cause significant harm to children and young people. We introduced a regular intervention - a prescribing safety huddle called the 'Druggle' that aims to a) increase the awareness of prescribing errors among doctors and nurses; b) improve prescribing and reduce errors and c) create a safe and positive prescribing culture. Method: We have presented a monthly 'Druggle' at our Clinical Risk Meetings, where prescribing errors are discussed and learning points identified. These interactive sessions also involve prescribing quizzes created by our pharmacist. We have collected regular feedback from the multidisciplinary team to enable us to continually improve the 'Druggle'. Data has been collected on prescribing errors on our paediatric ward, over 10 day periods in October 2018 and June 2019, before and after the introduction of the 'Druggle'. Results: We noted a decrease in prescribing errors from 187 to 126. Feedback from the MDT allowed us to alter the content of our 'Druggles' to focus on learning from reported prescribing related Clinical Incidents and to develop the idea of introducing a prescribing safety newsletter. It has also helped us to tailor prescribing teaching in induction for new doctors joining the department. We have recently incorporated a pharmacist-led daily drug huddle in our board rounds. Conclusion: Regular prescribing interventions like 'Druggles' could be a valuable tool to improve safety and reduce prescribing errors. Regular feedback can continuously improve and develop these interventions.